Andrographis paniculata (Burm.f.) Nees Leaf Extracts Lack Antibacterial Activity against some Bacterial Triggers of Inflammatory Diseases and are Non-toxic in vitro - Batten, Jason; Cock, I E (Asian Journal of Biological and Life Sciences)
Introduction: The recent development of extensively antibiotic resistant bacteria has necessitated the search for novel antibacterial compounds. An examination of aromatic plants and traditional medicines is an attractive option for drug discovery. Andrographis paniculata (Burm.f.) Nees is used in southern Asian traditional medicine for a variety of purposes and has been reported to have antibacterial activity against a limited panel of bacteria. Methods: The ability of A. paniculata leaf extracts to inhibit the growth of a panel of bacterial pathogens which can trigger some autoimmune diseases in genetically susceptible people was investigated by disc diffusion assays. Toxicity was examined using the Artemia franciscana nauplii bioassay. Results: Andrographis paniculata leaf solvent extracts of varying polarity were completely ineffective at inhibiting the growth of some bacterial triggers of autoimmune inflammatory diseases. The extracts were nontoxic in the Artemia nauplii bioassay following 24hr exposure. Conclusion: Andrographis paniculata leaf extracts were completely ineffective bacterial growth inhibitors against the tested pathogens. However, these extracts may have other therapeutic properties and testing against other bacterial pathogens, protozoa, viruses and tumour cells is required.
Keywords: Acanthaceae; Andrographis; Green chiretta; Antibacterial activity; Antibiotic resistant bacteria; Medicinal plants; Toxicity.